Find Out Who You Really Are: Adult Learning In Virtual Worlds - Elisabeth Hayes (Adult Education Research Conference, 2002)
Videogaming is a widely popular pastime in present society, particularly among young adults. Identifying the ways that these games support learning can broaden our understanding of how adults acquire knowledge, explore new identities, develop new skills and abilities. This paper analyzes one computer videogame to illustrate attributes of learning in a game-based environment.